Influence of environment on the storage quality of seed physiological amaranth - Nobre, Danúbia Aparecida Costa; David, Andréia Márcia Souza Santos; Souza, Vinícius Natanael Ribeiro; Oliveira, Dario; Gomes, André Angelo Medeiros; Aguiar, Patrick Mendes; Mota, Wagner Ferreira (Comunicata Scientiae, 2013)
The objective of this study was to evaluate the influence of the storage environment on quality of amaranth seed. The seeds were placed in polyethylene bags and stored for ten months in cold and in laboratory conditions. To evaluate the physiological quality of seeds, we determined the water, the one hundred seed weight, germination and vigor. The storage of amaranth in the cold chamber was more efficient for the conservation of physiological seed quality.